PENERAPAN MODEL CASE – BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH TSANAWIYAH NEGERI 2 MUARO JAMBI - Putri Elvie Nabila; Khoirul Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the application of the Case-Based Learning method in improving student learning outcomes in the Akidah Akhlak subject at MTs Negeri 2 Muaro Jambi. The type of research used is classroom action research (PTK) conducted in 2 cycles. The subjects studied were ninth-grade students, totaling 21 students. The data collection techniques used by the researcher were through direct observation, interviews, tests, and documentation. The pre-cycle results or initial observations showed that the number of students scoring above the KKM was only 43%. With the low number of students whose test results were below the KKM reaching 67%, the researcher chose this title. Furthermore, after conducting further learning using the case-based learning method, in cycle I, the percentage of students reaching the KKM score was 60%. This result was considered insufficient to be regarded as successful in the study. Subsequently, in cycleُII,ُtheُpercentageُofُstudentsُachievingُaُscoreُ≥KKMُwasُ85%. From the data, it can be seen that the implementation of the Case Based Learning method in the Aqidah Akhlak lesson can improve the learning outcomes of students at MTs Negeri 2 Muaro Jambi. In addition, this method can also increase students' motivation, activeness, and cooperation in the classroom. Thus, it can be concluded that the implementation of the Case Based Learning method to improve student learning outcomes in the Aqidah Akhlak subject at MTs Negeri 2 Muaro Jambi is successful. Keywords : the case based learning method improves learning outcome